Game design : behind the scenes - Hackett, Jennifer (New York : Children's Press, 2018)
Learn how video games are designed and find out how you can create games of your own.
Includes bibliographical references (page 45) and index.
6.3
3-6
STEAM collection. Some copies purchased with funds from the Corvallis Public Schools Foundation.
Keywords: Computer games -- Design -- Juvenile literature; Video games -- Design -- Juvenile literature; Computer games -- Design; Video games -- Design